PENERAPAN ANALISIS SWOT TERHADAP STRATEGI PEMASARAN USAHA MINUMAN KAMSIA BOBA MILIK ABDULLAH DI TENGAH PANDEMI COVID-19 DI KABUPATEN BANGKALAN - Fahmi Fadlillah Syaiful; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2020)
Nowadays the world is shocked with the spread of covid-19 which originated in China which then spread throughout the world including Bangkalan Regency. Abdullah as the business owner of Kamsia Boba precisely on the road RE Martadinata issued a marketing policy during this pandemic. The existence of this pandemic caused sales to plummet with the policy issued by Abdullah for the marketing management of his beverage business gradually his business sector was able to survive and remain effective